Extraction, purification and characterization of a thermally stable aspartic protease from freshwater shrimp Gammarus sp. with a high catalytic efficiency. (November 2021) - Mohammadi, Soheila; Azadi, Mohammad Ali; Hemmati, Roohullah; Homaei, Ahmad
Abstract: In the curent study, a new aspartic protease is purified by pepstatin A affinity chromatography from freshwater amphipod Gammarus sp. The molecular weight of the enzyme was determined by SDS-PAGE which estimated to be 55 kDa. Optimal temperature and pH were 55 °C and 6, respectively. According to our results, calculated KM and Vmax for azocasein substrate were 0.05 μg mL −1 and 4.2 μmol min −1 while those of casein substrate were 0.006 μg mL −1 and 1.1 μmol min −1 respectively. The values of kcat constants for azocasein and casein substrates were calculated to be 2583 s −1 and 686 s −1 respectively. Moreover, the catalytic efficiencies (kcat /KM ) for azocasein and casein substrates were 51, 167 and 114, 333 s −1 μg −1 .ml respectively. The estimated Δ H D #, Δ G D # and Δ S D # were 4.221 kcal mol −1, 24.18 kcal mol −1 and 70 cal mol −1 K −1 respectively. The values of Δ G E − S # in the presence of azocasein and casein were −1.74 and 2.97 kcal mol −1 and those of Δ G E − T # for azocasein and casein were - 6.29 and - 6.76 kcal.mol −1 respectively. Altogether, according to the obtained results, the new aspartic protease is thermally stable and catalytically efficient having a high affinity to milk casein as substrate and thus it has potential to be used in dairy industries for milk clotting. Highlights: A novel thermally stable aspartic protease was purified from Gammarus sp. The optimum temperature and pH of the enzyme are 55 °C and 6 respectively. The enzyme showed wide pH profile from 2 to 10 and wide thermal profile from 0 to 73 °C. The enzyme showed higher pH stability at pH values 6 and 9 compared with 3. The enzyme showed high catalytic efficiency for casein (114, 333 s −1 μg −1 .ml).